2017
DOI: 10.1080/09613218.2017.1307015
|View full text |Cite
|
Sign up to set email alerts
|

The influence of personality on user satisfaction: multi-tenant offices

Abstract: Many different multi-tenant offices have arisen over the last decades, as building owners address the changing nature of the workplace -a need for users to share facilities. However, the existing literature on multi-tenant buildings from the point of view of user satisfaction is scarce, limiting input for user-centred design. This study analyses the influence of personality on user satisfaction with multi-tenant office characteristics. Data were collected through a questionnaire distributed among users of 17 d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(30 citation statements)
references
References 39 publications
3
27
0
Order By: Relevance
“…However, research on users' preferences for characteristics of coworking spaces is still limited. One of the few studies on the characteristics of multi-tenant offices in general focused on user satisfaction, which is related to user preferences (Hartog, Weijs-Perrée, & Appel-Meulenbroek, 2017). Several physical characteristics of multi-tenant offices were divided into 10 important multi-tenant office factors, namely: location, office exterior and division, office decor, facilities and services, seclusion rooms, office leisure, information and communication technology (ICT) and equipment, privacy and office climate.…”
Section: User Preferencesmentioning
confidence: 99%
See 2 more Smart Citations
“…However, research on users' preferences for characteristics of coworking spaces is still limited. One of the few studies on the characteristics of multi-tenant offices in general focused on user satisfaction, which is related to user preferences (Hartog, Weijs-Perrée, & Appel-Meulenbroek, 2017). Several physical characteristics of multi-tenant offices were divided into 10 important multi-tenant office factors, namely: location, office exterior and division, office decor, facilities and services, seclusion rooms, office leisure, information and communication technology (ICT) and equipment, privacy and office climate.…”
Section: User Preferencesmentioning
confidence: 99%
“…Hereby, the choice options were self-employed worker, freelancer or entrepreneur; employee of a small company (2-10 employees); employee of a medium-sized company (11-50 employees); employee of a large company (more than 50 employees); and student. These user groups were selected based on previous research on co-working spaces (Deijl, 2011;Hartog et al, 2017;Kojo & Nenonen, 2014;Moriset, 2013). Respondents were also asked to indicate their position in the organization whereby they could choose between supporting staff, regular employee, manager, board member/owner or does not apply.…”
Section: User Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to effects of the workspace, work environment satisfaction research generally also includes the direct effects of personal characteristics such as age and gender, which have been shown to be significant (e.g., Bodin-Danielsson & Bodin, 2008;De Been & Beijer, 2014). Hartog, Weijs-Perrée, and Appel-Meulenbroek (2018) also found that personality affects satisfaction with the work environment in multi-tenant offices. Also, as ABOs have different types of workspaces for different activities, it can be assumed that an employee's activities could influence work environment satisfaction (De Been & Beijer, 2014).…”
Section: Theoretical Framework 1direct Effects On Satisfactionmentioning
confidence: 99%
“…Other studies have highlighted the importance of personality traits. In particular, introversion-extraversion has received significant research attention, with studies showing that introverts are more dissatisfied and disrupted than extraverts in the presence of background noise in general (Geen, 1984) and in open-plan offices in particular (Hartog et al, 2018;Oseland and Hodsman, 2018). Researchers have also considered the role of sensory processing sensitivity, an innate trait concerning the individual's sensitivity to external stimuli.…”
Section: Non-uniformity In Workplace Requirementsmentioning
confidence: 99%